Critical analysis of extra peritoneal antero-lateral approach for lumbar plexus - Roberto Sérgio Martins; Bernardo Assumpção Monaco; Mario Gilberto Siqueira; Luciano Foroni; Carlos Otto Heise; Manoel Jacobsen Teixeira (Arquivos de Neuro-Psiquiatria)
Lesions of lumbar plexus are uncommon and descriptions of surgical access are derived from vertebral spine approaches. METHOD: The extraperitoneal anterolateral approach to the lumbar plexus was performed in six adult fresh cadavers. The difficulties on dissection were related. RESULTS: An exposure of all distal elements of lumbar plexus was possible, but a cranial extension of the incision was needed to reach the iliohypogastric nerve in all cases. Ligation of vessels derived from common iliac artery was necessary for genitofemoral and obturator nerves exposure in two cases. The most proximal part of the lumbar roots could be identified only after dissection and clipping of most lumbar vessels. CONCLUSION: The extraperitoneal anterolateral approach allows appropriate exposure of terminal nerves of lumbar plexus laterallly to psoas major muscle. Cranial extension of the cutaneous incision may be necessary for exposure of iliohypogastric nerve. Roots exposure increases the risk of vascular damage.